Peter Mathers interviewed by Hazel de Berg for the Hazel de Berg collection - Mathers, Peter, 1931-2004; De Berg, Hazel, 1913-1984. (1969)
Mathers speaks of his childhood in Rose Bay; about his book "Trap".
Also available online
Tanscript available (6 p.)
Keywords: Mathers, Peter, -- 1931-2004.; Mathers, Peter, -- 1931-2004 -- Interviews; Novelists, Australian -- Interviews